Cloning, Expression And Immunogenicity Of Recombinant Bacille Calmette-Guerin (BCG) Containing T And B Cell Epitopes Of Mycobacterium Tuberculosis [QR82.M95 R737 2008 f rb]. - Mohamud, Rohimah (2008)
Tuberculosis (TB) remains one of the leading causes of morbidity and mortality in humans. The only TB vaccine currently available is an attenuated strain of Mycobacterium bovis, bacille Calmette–Guerin (BCG).